SOSIALISASI PELAKSANAAN PROTOKOL KESEHATAN DEMI MENINGKATKAN KESADARAN MASYARAKAT DALAM PENANGGULANGAN WABAH COVID-19 SERTA TATA CARANYOBLOS PEMILU DI ERA PANDEMI COVID-19 DI DESA PENATIH DANGIN PURI KECAMATAN DENPASAR TIMUR KOTA DENPASAR - BALI - I Wayan Sugiartana; I Made Adi Suwandana; I Wayan Suweca (Jurnal AKSES, 2021)
The study focuses om socializing the implementation of health protocol in order to increase public awareness in dealing with the covid-19 outbreak and the procedures for voting for elections in the era of the covid-19 pandemic in Dangin Puri Village, East Denpasar District, Denpasar City-Bali. During the current pandemic, the implementation of elections is very vulnerable to the transmission of the covid-19 election cluster. The Bali provincial government program has implemented a new era order protocol program since July 5, 2020, which is stated in the circular letter of the governor of Bali No. 3355 of 2020. However, when viewed from the situation on the ground, there are still many people who do activities outside their homes without implementing health of protocols. The government has made every effort to reduce the number of new cases or the number of spread of this disease. The success of the new era order protocol program launched by the government will not succeed if there is no cooperation and high understanding among the community to help the success of the new era order protocol program